Clinical characteristics of acute kidney injury in the first 13 critically ill patients infected with SARS-CoV-2 (COVID-19) at a peruvian hospital; a preliminary report - Benites-Flores, Irwing R. (2021)
Introduction: The high transmissibility and lethality of the novel coronavirus SARS-CoV-2 (COVID-19) have been catastrophic. Acute kidney injury (AKI) is one of the frequent complications in patients with respiratory insufficiency caused by the virus. The pathogenic mechanism is based on the binding of its S-proteins to the angiotensin-converting enzyme (ACE) receptors, which will trigger a cellular damage. A podocyte and tubular compromise are found in the kidneys which can lead to tubular necrosis and the consequent AKI. Objectives: The objective of this report is to identify the main risk factor to develop AKI in patients infected with SARS-CoV-2 with critical acute respiratory distress. Patients and Methods: We performed this report study, collecting data from 48 ICU patients. Data from 13 of them who developed AKI and needed renal replacement therapy (RRT)were analyzed. Clinical characteristics and laboratory findings were reported using STATA 10.0. Results: AKI was present in 27.08% of patients, mostly male (92.3%) with a mean age of 63.8 years old. Hypertension, diabetes and obesity were the main comorbidities in those patients. Additionally, the meantime between admission and AKI diagnosis was 2.69 days. All patients showed fibrinogen, D-dimer, ALT and values above normal range. Mortality was seen in 61.5% of patients. Conclusion: This report tries to show AKI as an important clinical manifestation in critically ill patients infected with SARS-CoV-2, with high mortality. Further studies are needed to demonstrate if there are independent risk factors.